Security Collapse in the HTTPS Market. - ARNBAK, AXEL; ASGHARI, HADI; VAN EETEN, MICHEL; VAN EIJK, NICO (Communications of the ACM, 2014)
The article offers the author's view on the fall of security in the hypertext transfer protocol secure (HTTPS) market. He mentions its role in web browsing security as well as the manifestation of Internet services and users through a certificate-based authentication protocol. He notes its criticality in protecting online activities of economy, society and politics. An overview of security breach at certificate authorities (CAs) such as DigiNotar BV, Comodo Group Inc. and Verisign Inc. is also presented.